(untitled) (Global Journal of Science Frontier Research, 2017)
Nine tomato cultivars comprising Tropimech (T1), Carl J (T2), Peto 86 (T3), Roma (T4), UC82B (T5), Chibli (T6), Heinz (T7), NI (T8) and RIO (T9) were evaluated for energy use efficiency, economic analysis, residue deposits, agronomic efficiency, nutrient tolerance and yield performance under four fertilizer rates. The trial was conducted at the Kadawa irrigation site of Kano State altitude 476.2m, Lat.11.550N and Long. 8.380E. Nursery sowing and transplanting were carried out on 10 November, 2015 at a minimum temperature of 160C and on 22 December 2015 at a minimum temperature of 13.40C. Fertilizer treatment was applied at 0, 170, 200,230 and 260 kgha-1(20-10-10) respectively under the basin size of 25m2 and 0.5m x 0.5m spacing. Irrigation water was supplied evenly at the flow rate of 11 m3hr-1 using 3” diameter pressurized rubber tube at an average discharge rate of 10.87 m3-hr. Results obtained indicated that the total energy budget for the production of the nine cultivars was 112,180.55 MJha-1 with fertilizer accounting for about 41.2% of the energy input. Energy use efficiency was however low showing inefficient us of energy in tomato production typical of Nigerian system. T2, T4, T5, T6 and T7 recorded agronomic efficiency of 8.05, 14.10, 2.38, 4.53, and 13.96 with a corresponding yield performance of 20.6, 24.8, 19.4, 20.1 and 24. 4 tha-1 respectively. Residue deposits were significantly more pronounced with T4, T7, T9, T3, and T2 possibly suggesting cultivars with higher concentration of ethanol than others at 7.88 tha-1, 5.99 tha-1, 4.85 tha-1, 4.75 tha-1, and 4.62 tha-1 respectively. The highest nutrient limited tolerance index (TOLN) was observed in T4 followed by T7, T6 and T5, revealing the cultivars with the possibility of early segregation , although displaying the characteristics of initial better yield performance in contrast to T2 with more stable traits as observed in low TOLN with higher yield at both optimal and limited fertilizer rat